Apalutamide and overall survival in prostate cancer - Smith, Matthew R.; Saad, Fred; Chowdhury, Simon; Oudard, Stéphane; Hadaschik, Boris; Graff, Julie N.; Olmos, David; Mainwaring, Paul N.; Lee, Ji Youl; Uemura, Hiroji; De Porre, Peter; Smith, Andressa A.; et al. (European urology, 2021)
Background - The phase 3 SPARTAN study evaluated apalutamide versus placebo in patients with nonmetastatic castration-resistant prostate cancer (nmCRPC) and prostate-specific antigen doubling time of ≤10 mo. At primary analysis, apalutamide improved median metastasis-free survival (MFS) by 2 yr and overall survival (OS) data were immature. - Objective - We report the prespecified event-driven final analysis for OS. - Design, setting, and participants - A total of 1207 patients with nmCRPC (diagnosed by conventional imaging) were randomised 2:1 to apalutamide (240mg/d) or placebo, plus on-going androgen deprivation therapy. After MFS was met and the study was unblinded, 76 (19%) patients still receiving placebo crossed over to apalutamide. - Outcome measurements and statistical analysis - OS and time to cytotoxic chemotherapy (TTChemo) were analysed by group-sequential testing with O’Brien-Fleming-type alpha spending function. - Results and limitations - At median 52-mo follow-up, 428 deaths had occurred. The median treatment duration was 32.9 mo for apalutamide group and 11.5 mo for placebo group. Median OS was markedly longer with apalutamide versus placebo, reaching prespecified statistical significance (73.9 vs 59.9 mo, hazard ratio [HR]: 0.78 [95% confidence interval CI, 0.64-0.96]; p=0.016). Apalutamide also lengthened TTChemo versus placebo (HR: 0.63 [95% CI, 0.49-0.81]; p=0.0002). Discontinuation rates in apalutamide and placebo groups due to progressive disease were 43% and 74%, and due to adverse events 15% and 8.4%, respectively. Subsequent life-prolonging therapy was received by 371 (46%) patients in the apalutamide arm and by 338 (84%) patients in the placebo arm including 59 patients who received apalutamide after crossover. Safety was consistent with previous reports; when adverse events were adjusted for treatment exposure, rash had the greatest difference of incidence between the apalutamide and placebo groups. - Conclusions - Extension of OS with apalutamide compared with placebo conferred impactful benefit in patients with nmCRPC. There was a 22% reduction in the hazard of death in the apalutamide group despite 19% crossover (placebo to apalutamide) and higher rates of subsequent therapy in the placebo group. - Patient summary - With data presented herein, all primary and secondary study end points of SPARTAN were met; findings demonstrate the value of apalutamide as a treatment option for nonmetastatic castration-resistant prostate cancer.
Available online 6 September 2020
Gesehen am 02.02.2022